ANALISIS KINERJA BANK SYARIAH MANDIRI - Lisa Narulia; Suryadi HS (Majalah Ilmiah Ekonomi Komputer, 2006)
An outstanding growth of Syariah Bank in Indonesia has stimulate a stricht competition among bank in Banking environment. Since the competition so stricht each bank has so increase its performance continously. By that reason, each of banks management should analyze their performance so that they can predict what they should do to increase the next performance. For Syariah Bank, FATWA MUI No. 1 about the law of Riba will influence bank's performance because it is giving a new way of thinking about Syariah Bank in social environment. Information services based on computer application are another technique to increase bank performance, so the bank's management should put special attention into this aspect either. Keyword : Syariah Bank, Financial Ratio